Kontribusi layanan bimbingan kelompok terhadap pencegahan perilaku beresiko pada siswa - Masnurrima Heriansyah (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2018)
Student life is adjacent to risky behaviors that can lead to mental health disorders such as smoking, alcohol consumption, drug addiction and pre-marital sexual intercourse. Risk behavior that can disrupt these students need to be prevented so that students do not do things negative in life. This study aims to determine the contribution of group guidance services in preventing risky behavior on the students. This study uses quantitative ex post facto method with correlational descriptions and a sample of 65 students. The results showed that group guidance services showed a contribution in preventing risky behavior in students by 35% so that group counseling services can be used as a prevention strategy for risky behavior and provide a positive understanding for students about the negative impact of risk behavior. The implications of the research are to provide an overview of the importance of counseling and guidance services in the form of prevention and for students to recognize and understand and not to engage in risky behaviors that can damage them